2011
DOI: 10.1007/s12070-011-0163-4
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media with Effusion in Relation to Socio Economic Status: A Community Based Study

Abstract: Otitis media with effusion (OME) is the presence of non purulent effusion within the middle ear cleft. The symptoms of this disease are not alarming as in suppurative otitis media. The disease is common in young children. The main symptom of this disease is decreased hearing, which may sometime go unnoticed more so if the parents are not attentive. We conducted a community based study among 1,020 school children of the age group 5-10 years from schools of sub-urban areas of Dakshina Kannada district, Karnataka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Otitis media is an infectious disease widely found around the world. In the United States, it represented 42% of antibiotic treatment prescribed in ambulatory [4].…”
Section: Introductionmentioning
confidence: 99%
“…Otitis media is an infectious disease widely found around the world. In the United States, it represented 42% of antibiotic treatment prescribed in ambulatory [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chonmaitree's study [10] stated that otitis media occurred to more than 60% of young children who had a viral upper respiratory infection. Although considered a mild condition, otitis media with effusion decreases hearing acuity [11] .…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Ologe (2003), chronic otitis media in rural public elementary schools was 6% in 699 children compared to 0% in 270 children in urban private elementary schools [3] . When it comes to effect of the economic status on the prevalence of otitis media, some studies reported that the lower the income, the higher the prevalence of otitis media [11] .…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the common causes of deafness among children. When inadequately treated, it may lead to major functional limitations like hearing loss and impairment in development of speech and language [1]. The reason for treatment failure is probably due to partial knowledge of etiopathological mechanisms responsible for the beginning and the course of the disease in the mucous membrane of the middle ear [2].…”
Section: Introductionmentioning
confidence: 99%